What can management option uptake tell us about ecosystem services delivery through agri-environment schemes?. (February 2019) - Arnott, David; Chadwick, David; Harris, Ian; Koj, Aleksandra; Jones, David L.
Highlights: AES funding only represented a small proportion (<15%) of total agricultural support. Majority of AES payments to farmers were small (<£10k year-1). AES options uptake is heavily biased towards habitat and livestock management. The AES had no overarching impact assessment or measurable outcomes. Prescriptive nature of AES limits the ability to promote long-term behavioural change. Abstract: Agri-environment schemes (AES), currently embedded in EU and UK policies, actively promote 'greening', 'sustainability' and 'ecosystem services' approaches to land management. The funding structures of these policies, however, run counter to this sustainable approach, and create barriers to AES success, primarily through a continued focus on productivity support. In this study, we aim to determine the effectiveness of action-based AES, as a delivery mechanism for ecosystem services, using secondary data analysis techniques to unravel the complexities of AES funding distribution and scheme structure and geographic information systems (GIS) to explore the spatial extent and uptake of AES management options, using Wales, UK as a study area. Our results show 84% of recipients of AES payments receiving <£10k annually, comprising only 35% of the total available funding. 15, out of a total of ∼165, management options, accounted for >75% of all advanced level management contracts awarded in both 2015 and 2017. This bias in option uptake, in many cases, positively prevents further deterioration of existing habitat condition through a 'business as usual' approach. However, we argue that the voluntary, over prescriptive nature of the schemes limits management option uptake, negatively impacts on the schemes ability to deliver ecosystem services, and lessens the government's ability to promote long-term behavioural change. If AES are to deliver the '"Public Goods"' that future policy demands, then targeted and adequate levels of funding and a willingness to participate must be combined with greater farmer autonomy and clear outcomes to deliver management options at a landscape scale.